Spontaneous arterial dissection: phenotype and molecular pathogenesis - Grond-Ginsbach, Caspar; Pjontek, Rastislav; Aksay, Suna Su; Hyhlik-Dürr, Alexander; Böckler, Dittmar; Groß-Weissmann, Marie-Luise (Cellular and molecular life sciences, 2010)
Arterial dissection (AD) is defined as the longitudinal splitting up of the arterial wall caused by intramural bleeding. It can occur as a spontaneous event in all large and medium sized arteries. The histological hallmark of AD is medial degeneration. Histological investigations, gene expression profiling and proteome studies of affected arteries reveal disturbances in many different biological processes including inflammation, proteolytic activity, cell proliferation, apoptosis and smooth muscle cell (SMC) contractile function. Medial degeneration can be caused by various rare dominant Mendelian disorders. Genetic linkage analysis lead to the identification of mutations in different disease-causing genes involved in the biosynthesis of the extracellular matrix (FBN1, COL3A1), in transforming growth factor (TGF) beta signaling (FBN1, TGFBR1, TGFBR2) and in the SMC contractile system (ACTA2, MYH11). Genome wide association studies suggest that the CDKN2A/CDKN2B locus plays a role in the etiology AD and other arterial diseases.